Biomechanical evaluation of a novel mandibular distraction osteogenesis protocol: an in-vitro validation and the practical use of the method. Issue 7 (19th May 2021) - Şensoy, A. T.; Kaymaz, I.; Ertaş, Ü.
Abstract: The aim of this study was to optimize and experimentally validate the certain parameters affecting the operation success of Mandibular Distraction Osteogenesis (MDO). According to FEA results, the displacement of the samples showed 28.5% reduction as only the osteotomy line was separately optimized, and 64.2% less displacement was determined when the osteotomy line and the screw configuration were optimized together. In consistent with the FEA results, the samples showed 62% and 84.5% fewer displacement values, respectively. As a result, the MDO protocol suggested, which is validated by both numerical and experimental studies, offers promising outcomes for operation success.